Q: P equals b plus 3a plus c solve for b?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x+a=p 2x=p-a x=.5p-.5a

p is obviously zero because any number x plus 0 equals itself.

x = (P - 2W) / 2

16.52 + p = 495.50 p = 495,50 - 16,52 p= 478,98

you multiply m n p

Related questions

2x+a=p 2x=p-a x=.5p-.5a

P = 3a - 3q Add 3q to each side: P + 3q = 3a Double each side: 6a = 2P + 6q

p is obviously zero because any number x plus 0 equals itself.

x = (P - 2W) / 2

16.52 + p = 495.50 p = 495,50 - 16,52 p= 478,98

3 + P = 8 Therefore: P = 8 - 3 P = 5

You can combine like terms of p to get 6p. If you are given what p equals you can solve for the completely numerical answer.

you multiply m n p

You don't have enough information to solve this. You need to know what P is, or what T is, otherwise you can't get an answer.

2

A = P + P Y TSubtract 'P' from each side:A - P = P Y TDivide each side by PT :Y = (A - P) / PT

Subtract 2a from each side: P - 2a = b ie b = P - 2a